Вы находитесь на странице: 1из 11

2

2.
n.

AA B

1 d [ A]
= k[ A]n ;
A dt

(1)

d [ A]
= kdt ; A = 1
n
[ A]

(2)

, t=0

= 0.

d [ A]
1
1 t
0 [ A]n = n 1 [ A]n1 0| = kt

(3)

1 1
1

= kt
n 1
n 1
n 1 [ A]
[ A0 ]

(4)

1
= f (t )
n 1
[ A]

n-1

1/[A]

tg = (n-1)*k, n>1

tg = (n-1)*k, n<1

. 1 n>1.

n < 1.
.
(4):

1
1 [ A0 ]n 1
*
1 = kt

n 1 [ A0 ]n 1 [ A]n 1

(5)

[ A0 ]n 1
n 1
=

t =
n 1
[ A]

(6)

1
1
n 1 1) = k
*
n 1 (
n 1 [ A0 ]

(7)

,
. :

1
n 1
ln
(n 1) * ln[ A0 ] + ln ( 1) = ln k + ln
n 1

(8)

const (n 1) * ln[ A0 ] = ln

(9)

ln

[A0] = ln .

(1-n) - n - .
ln

tg = (1-n), n<1

tg = (1-n), n>1

ln [A0]

. . 48-51, 160-162
. . 22-28, 356-359
.-. . 201-204, 345-346
n=2, (4)

1
1

= kt
[ A] [ A0 ]

(10)

[ A0 ]
1 + k[ A0 ]t

(11)

[ A] =

2
:

I + I = I2

(12)

[ I ](t ) =

[ I 0 ](t )
1 + k[ I 0 ]t

[I2 ] =

1
1
[I0 ]
{[ I 0 ] [ I ](t )} = [ I 0 ]

2
2
1 + k[ I 0 ]t

1
= f (t ) .
[ A]

2
1
1
=
= kt1/2
[A 0 ] [A 0 ] [A 0 ]

(13)

t1/2 =

1
[A 0 ]*k

A+B

(14)
AB, C+D

-d[A]/dt = - d[B]/dt = k [A] [B]

(15)

[A] = [A0] x; [B] = [B0] x

(16)

- d[A] = dx

(17)

[A0],[B0] - .
:

dx
= kdt
([ A0 ] x ) * ([ B0 ] x )

(18)

, (18),
.

dx
=
([ A0 ] x ) * ([ B0 ] x )
dx

dx
1
*

([ B0 ] [ A0 ]) ([ A0 ] x ) ([ B0 ] x )

(19)

, :
t

| |

([ B ] x )
1
* ln 0
= kt
([ B0 ] [ A0 ]) ([ A0 ] x ) 0 0
t

(20)

=0 (20) , = 0,
5

([ B0 ] x )
([ B0 ])
1
* ln
ln
= kt

B
A
A
x
A
[
]
[
]
[
]
[
]

( 0
) ( 0 )
( 0
0 )

(21)

([ B])
([ B0 ])
ln
[
B
]
[
A
]
*
k
*
t
ln
=

+
( 0

0 )
[
A
]
[
A
]
(
)
(
)
0

ln

ln [0]/[0]

(22)

{[B]/[A]}= f(t)

tg = k*{[B0]-[A0]}
[B0]>[A0]

ln []/[]

tg = k*{[B0]-[A0]}

ln [0]/[0]

[B0]<[A0]

, . -
.
(21)

[ x] = f (t )

1 exp ({[ B0 ] [ A0 ]} kt )
[ x] = [ B0 ]
[B ]
1 exp ({[ B0 ] [ A0 ]} kt ) 0
[ A0 ]
[ A0 ] > [ B0 ], t ,[ x] [ B0 ] , [ B0 ] > [ A0 ], t ,[ x] [ A0 ]

.
,

+B 2B; -d[A]/dt = d[B]/dt = k [A] [B]

(23)

,
.
(23):

[A] = [A0] x; [B] = [B0] + x


- d[A] = dx

(24)

dx
= kdt
([ A0 ] x ) * ([ B0 ] + x )

(25)

dx
=
([ A0 ] x ) * ([ B0 ] + x )
dx

1
dx
+
*

([ B0 ] + [ A0 ]) ([ A0 ] x ) ([ B0 ] + x )

(26)

| |

([ B0 ] + x )
1
* ln
= kt
([ B0 ] + [ A0 ]) ([ A0 ] x ) 0 0

(27)

([ B ])
1
([ B0 ])
* ln
ln
= kt

([ B0 ] + [ A0 ]) ([ A]) ([ A0 ])

(28)


ln []/[]

A +B = 2B

ln [0]/[0]

tg = k*{[B0]+[A0]}

[ x] = g (t )

.
(15) (23).
.

dx
= k ([ A0 ] x )([ B0 ] x )
dt
dx
= k1 ([ A0 ] x )([ B0 ] + x )
dt
d 2x

.
2
dt

2
[ A0 ] ,

[ B0 ] , .
.
.
. ,

[ A0 ] , [ B0 ] , !

.
. . 51-53

C+D

(29)
9

-d[A]/dt = d[C]/dt = k [A]0 = k

(30)

[A0] - [A] =[C] - [C0] = k*t

(31)

[A]

[A0]

tg = - k

2N2O 2N2 + O2

(32)

.
N2O :

r = -d[N2O]/dt = k

(33)

, . N2O
0, N2O
N2O .

d [ N 2O ]gas
dt

= k '[ N 2O ]sur = k ''

10

2 N2O --> 2 N2 + O2

r = k"

p N2O

pN O
2

11